Drag reduction by a multi-point optimised hybrid flow control method for two supercritical airfoils - Nejati, A.; Mazaheri, K. (European Journal of Computational Mechanics, 2016)
Shock control bump (SCB), suction and blowing are three flow control methods used to control the shock wave/boundary layer interaction to reduce the resulting wave drag in transonic flows. An SCB uses a small local surface deformation to reduce the shock wave strength, while the suction decreases the boundary layer thickness and the blowing delays the flow separation. Here, we will use a multi-point continuous adjoint optimisation scheme to find the optimum design of suction and blowing separately or together, or with the SCB, on two supercritical airfoils, i.e. RAE-5225 and RAE-2822, for a wide range of off-design transonic Mach numbers. The RANS flow equations are solved using the Roe’s averages scheme. The independent usage of the SCB, the suction and the blowing methods has resulted in the average aerodynamic performance improvement of, respectively, 11.7, 4.16, and 4.21%, with respect to the clean RAE-5225 airfoil and for the RAE-2822 these numbers are 11.1, 4.04, and 6.61%, respectively. The simultaneous usage of suction with blowing results in 8.61% improvement of the average aerodynamic efficiency for the RAE-5225, while this increase is 7.63% for the RAE-2822. The hybrid usage of all three methods improves the average aerodynamic performance by 17.7% for the RAE- 5225 and 22.1% for the RAE-2822. It is shown that the suction does not change the shock wave position significantly, but the blowing moves it forward, and reduces or removes the separated region after the shock wave or the SCB.